The Relationship between Shift Work Patterns and Mental Health of Health Workers in Hospitals - Afif Wahyudi Hidayat (Miracle Journal Get Press, 2025)
Employees in the healthcare industry are crucial to guaranteeing that patients receive high-quality care.  The shift work pattern used in hospitals to provide 24-hour service is one of the biggest issues facing healthcare professionals.  In addition to identifying mitigating strategies that might be used to enhance healthcare workers' well-being, this study intends to investigate the link between shift work patterns and the mental health of hospital healthcare professionals.  Techniques.  Health professionals who worked in hospitals with shift work arrangements participated in a cross-sectional research.  Logistic regression and the chi-square statistical test were used to analyze the data. The bivariate analysis's findings demonstrated a strong correlation between the health worker's mental health and their shift patterns.  Compared to individuals who worked regular hours, health workers with irregular shift patterns experienced greater levels of moderate sadness (58.3%), high anxiety (66.7%), and sleep disruption (83.3%).  There is a statistically significant correlation between shift patterns and mental health, as indicated by the significant p value (0.05).  Conclusions.  Working irregular shifts can have a detrimental effect on a health worker's health, increasing their risk of anxiety, depression, and sleep issues.